Electrostatic dust cloth: a new sampling method for occupational exposure to bioaerosols - Viegas, Carla (2017)
Electrostatic dust cloth is an easy-to-use passive device that consists on a polypropylene cloth. This collection device is increasingly being used because it is electrostatic, inexpensive, easy to obtain, and effective at collecting dust. We intended to identify in scientific papers the use of electrostatic dust cloth to assess occupational exposure to bioaerosols and to conclude about its suitability to complement the exposure assessments done in the workplace environment. Literature research was performed using scientific and academic databases. Seven from the eight articles analysed were focusing indoor air quality assessments, and one article on occupational exposure. Three papers were reporting microbiota (bacteria and fungi) burden. Electrostatic dust collector gives a more complete occupational exposure scenario regarding bioaerosols, allowing a more rigorous assessment, since among other advantages they can collect contamination from a larger period of time.